The Self-concept Of Academic Ability That Affected by Some Variables Demography Of the Ninth Grade Students In Nablus Governorate Government Schools - Mufeed Nofal (My University, 1998)
The purpose of this study was to investigate the effect of the self- concept of academic ability by some demography variables of the Ninth Grade students in Nablus Government schools. The investigator aims at answering the following question: What is the level of self—concept of academic ability according to Ninth Grade students’ point of view? The study had the following hypotheses: 1- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to sex of the students. 2- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to place of resident. 3- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to educational background of the student’s father. 4- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to the educational background of student’s mother. In order to achieve the purpose of the study the investigator has applied the scale of self concept of academic ability designed by Brookover. Scale which included one instrument: 14 Items covered the self concept of Academic ability the population of the study consisted of (3526) students constituting the male and female students of the Ninth Grade students in (75) governmental schools in Nablus District. The sample of this study consisted of (392) male and female students which constitute 11% of the whole population. All of the sample have received the questionnaire and (383) were completed and analyzed in this study to analyze the data, the investigator used: 1-The mean values and degree of agreement for each item from the Items ofthe scale. 2-t-test for dependent groups. 3-One-Way analysis of variance. 4-(LSD) test. The results showed the following: I. Regarding the question of the study the results showed that the degree of agreement to the Ninth Grade students on the self- concept of academic ability was high (4,04-4,16) concerning the items (10,8,9,6,4). At the same time on the items (11,5,7,3,12,l3) was nearly highly (3,5-3,99) and it was between (3-3.49) on the items (2,14,1 ( ll. Regarding the hypotheses of the study, the result showed the following: 1-There are no significant differences at (α =0.05) between male and female students regarding the self concept of academic ability in the governmental schools of Nablus District. 2- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to place of resident. 3- There are significant difference at (α =0.05) between the mean sores responses of the Nintl1 Grade students in Nablus Governmental schools in scale of self concept of academic ability due to the educational background of students fathers. 4- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability that can be attributed to levels of mother’s education except the existed differences between (elementary education and college education) (secondary education and college education) and the differences over in favour of college education. In the light of the results of this study, a number of recommendations were made: 1-The researcher recommends that the Ministry of Education should take the results consideration in order to develop the self-concept of academic ability of the students. 2- The Ministry of Education is recommended to cooperate with counselors in governmental schools in order to strengths the self-concept of academic ability of the students through giving them private counseling Lessons. 3- The researcher recommends that curriculum designers should do their best in order to include certain curriculum activities that strengthen tl1e self-concept of academic ability of students.

The purpose of this study was to investigate the effect of the self- concept of academic ability by some demography variables of the Ninth Grade students in Nablus Government schools. The investigator aims at answering the following question: What is the level of self—concept of academic ability according to Ninth Grade students’ point of view? The study had the following hypotheses: 1- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to sex of the students. 2- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to place of resident. 3- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to educational background of the student’s father. 4- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to the educational background of student’s mother. In order to achieve the purpose of the study the investigator has applied the scale of self concept of academic ability designed by Brookover. Scale which included one instrument: 14 Items covered the self concept of Academic ability the population of the study consisted of (3526) students constituting the male and female students of the Ninth Grade students in (75) governmental schools in Nablus District. The sample of this study consisted of (392) male and female students which constitute 11% of the whole population. All of the sample have received the questionnaire and (383) were completed and analyzed in this study to analyze the data, the investigator used: 1-The mean values and degree of agreement for each item from the Items ofthe scale. 2-t-test for dependent groups. 3-One-Way analysis of variance. 4-(LSD) test. The results showed the following: I. Regarding the question of the study the results showed that the degree of agreement to the Ninth Grade students on the self- concept of academic ability was high (4,04-4,16) concerning the items (10,8,9,6,4). At the same time on the items (11,5,7,3,12,l3) was nearly highly (3,5-3,99) and it was between (3-3.49) on the items (2,14,1 ( ll. Regarding the hypotheses of the study, the result showed the following: 1-There are no significant differences at (α =0.05) between male and female students regarding the self concept of academic ability in the governmental schools of Nablus District. 2- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability due to place of resident. 3- There are significant difference at (α =0.05) between the mean sores responses of the Nintl1 Grade students in Nablus Governmental schools in scale of self concept of academic ability due to the educational background of students fathers. 4- There are no significant differences at (α =0.05) between the mean sores responses of the Ninth Grade students in Nablus Governmental schools in scale of self concept of academic ability that can be attributed to levels of mother’s education except the existed differences between (elementary education and college education) (secondary education and college education) and the differences over in favour of college education. In the light of the results of this study, a number of recommendations were made: 1-The researcher recommends that the Ministry of Education should take the results consideration in order to develop the self-concept of academic ability of the students. 2- The Ministry of Education is recommended to cooperate with counselors in governmental schools in order to strengths the self-concept of academic ability of the students through giving them private counseling Lessons. 3- The researcher recommends that curriculum designers should do their best in order to include certain curriculum activities that strengthen tl1e self-concept of academic ability of students.
مفهوم الذات الأكاديمي وتأثره ببعض المتغيرات الديموغرافية لدى طلبة الصف التاسع الأساسي في المدارس الحكومية في محافظة نابلس